A user configurable microtransaction system for free-to-play games - Augusto Carlos Avides Moreira Pinto Osório (2022)
The microtransaction system has been one of the most talked about aspects of video games that have been recently released, in which they have brought a diverse controversy between their monetization towards their consumers. With this dissertation we intend to create a microtransaction scheme that can monetize a game in a way that it is balanced and fair for different types of consumers, but at the same time bring benefits to the companies that practice it.